A Single-Extremity Staged Approach for Critical Congenital Heart Disease Screening: Results from Tennessee - William Walsh; Jean A. Ballweg (MDPI AG, 2017)
Tennessee initiated single-extremity staged screening by pulse oximetry for undetected CCHD in 2012. The algorithm begins with a saturation reading in the foot and allows an automatic pass if the foot pulse oximetry is 97% or greater. This was based on the principle that it is not possible to have a greater than 4% difference in the pulse oximetry between upper and lower extremities if the lower extremity is equal to or greater than 97%. This approach eliminates over 75,000 "unnecessary" pulse oximetry determinations in Tennessee each year without affecting the ability to detect CCHD before hospital discharge.